Hypertrophic cardiomyopathy: A review - Bazan, Silméia Garcia Zanati [UNESP]; de Oliveira, Gilberto Ornellas [UNESP]; da Silveira, Caroline Ferreira da Silva Mazeto Pupo [UNESP]; Reis, Fabrício Moreira [UNESP]; Malagutte, Karina Nogueira Dias Secco [UNESP]; Tinasi, Lucas Santos Nielsen [UNESP]; Bazan, Rodrigo [UNESP]; Hueb, João Carlos [UNESP]; Okoshi, Katashi [UNESP] (Sociedade Brasileira de Cardiologia, 2020)
Hypertrophic cardiomyopathy (HCM) is the most common heart disease with a genetic origin, and its main characteristic is left ventricular hypertrophy that occurs in the absence of other conditions that trigger this change. HCM may present from asymptomatic forms to manifestations of sudden cardiac death and severe heart failure. Contemporary high-resolution imaging methods and more accurate clinical scores have been used and developed to provide a prognostic assessment and adequate functional assessments, as well as to allow for the stratification of clinical severity. These aspects will be addressed in this review, along with other classic topics inherent to the study of this disease.
Cardiomiopatia Hipertrófica – Revisão
Keywords: Cardiomyopathy, hypertrophic/genetics; Echocardiography/methods; Heart failure; Hypertrophy, left ventricle; Sudden cardiac death